상업스포츠센터 종사원의 공감이 직무만족, 고객지향성, 서비스품질 및 조직충성도에 미치는 영향 - 김범; Buom Kim; 정정희; Jung-hee Jung (Ch'eyuk kwahak yŏn'gu, 2020)
[목적] 이 연구의 목적은 상업스포츠센터 종사원의 공감이 직무만족, 고객지향성, 서비스품질 및 조직충성도에 미치는 영향 관계를 구조방정식모형을 통해 실증적으로 분석하는 것이다. [방법] 서울지역에 소재한 11개소의 남녀 종사원 205명을 대상으로 하였다. 표본추출은 편의표본추출법과 설문지작성은 자기기입식으로 하였다. 제안한 구조모형을 검증하기 위해 IBM SPSSWIN Ver. 21.0과 AMOS 18.0을 사용하였다. [결과] 첫째, 인지적공감은 직무만족에 긍정적인 영향을 미쳤다. 둘째, 정서적공감은 직무만족에 긍정적인 영향을 미쳤다. 셋째, 커뮤니케이션공감은 직무만족에 긍정적인 영향을 미쳤다. 넷째, 직무만족은 고객지향성에 긍정적인 영향을 미쳤다. 다섯째, 직무만족은 서비스품질에 긍정적인 영향을 미쳤다. 여섯째, 직무만족은 조직충성도에 긍정적인 영향을 미쳤다. 일곱째, 고객지향성은 조직충성도에 긍정적인 영향을 미치지 않았다. 여덟째, 서비스품질은 조직충성도에 긍정적인 영향을 미쳤다. [Purpose] The purpose of this study was to empirically analyze the relationship between a commercial sports centers employees’ empathy, job satisfaction, customer orientation, service quality & organization loyalty through structural equation model analysis. [Methods] For this purpose, this study set 205 employees’ at the eleven commercial sports centers located in Seoul as the research subjects. In an effort to verify the proposed structural model, this study used IBM SPSSWIN Ver. 21.0 and AMOS 18.0. [Results] First, cognitive empathy had a positive effect on job satisfaction. Second, emotional empathy had a positive effect on job satisfaction. Third, communication empathy had a positive effect on job satisfaction. Fourth, job satisfaction had a positive effect on customer orientation. Fifth, job satisfaction had a positive effect on service quality. Sixth, job satisfaction had a positive effect on organization loyalty. Seventh, customer orientation didn’t had a positive effect on organization loyalty. eighth, service quality had a positive effect on organization loyalty.